Assessment-driven Learning through Serious Games: Guidance and Effective Outcomes - Othman Bakkali Yedri; Lotfi El Aachak; Mohamed Bouhorma (International Journal of Electrical and Computer Engineering (IJECE), 2018)
Evaluation in serious games is an important aspect; it aims to evaluate the good transmission of pedagogical objectives, the performance of student in relation to these objectives defined in the pedagogical scenario, the content of the course and the predefined criteria. However, the effectiveness of learning is under-studied due to the complexity involved to gamify the assessment concept, particularly when it comes to intangible measures related to the progression of learning outcomes, which is among the most important aspects of evaluation in serious games. This paper reviews the literature regarding assessment due to their importance in the learning process with a detailed assessment plan applied on serious game. Then, it presents a framework used to facilitate the assessment design integrated in serious games. Finally, a significant example of how the proposed framework proved successful with corresponding results will conclude the paper.